2016
DOI: 10.3233/wor-162267
|View full text |Cite
|
Sign up to set email alerts
|

An examination of retention factors among registered nurses in Northeastern Ontario, Canada: Nurses intent to stay in their current position

Abstract: This study shows that a further understanding of the work environment could assist with developing retention for rural nurses. Furthermore, employers may use such information to ameliorate the working conditions of nurses, while researchers may use such evidence to develop interventions that are applicable to improving the working conditions of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…LPNs may not be accorded the flexibility to determine their work activities or be able to influence their work environment. With the high turnover and low staff numbers in rural and remote settings (Nowrouzi 2015), it may be difficult to maintain a consistent and supportive work environment for LPNs. Managers and RN team members may take a default position of restricting LPN practice if they are not aware of the LPN scope or if they are not fully confident in the individual LPN's abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPNs may not be accorded the flexibility to determine their work activities or be able to influence their work environment. With the high turnover and low staff numbers in rural and remote settings (Nowrouzi 2015), it may be difficult to maintain a consistent and supportive work environment for LPNs. Managers and RN team members may take a default position of restricting LPN practice if they are not aware of the LPN scope or if they are not fully confident in the individual LPN's abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The need to separately study LPN and RN roles has been noted only recently (Harris and McGillis Hall 2012), and most researchers of staffing and staff mix have focused on urban settings (e.g., Duffield et al 2011;Lavander et al 2018). Studies of LPNs have addressed interactions with RNs (Huynh et al 2011;Lavander et al 2018), mobility (Harris et al 2013;Salami et al 2018), role differences (McClosky et al 2015), retention (Havaei et al 2016;Nowrouzi et al 2015) and redesigning teams (MacKinnon et al 2018;Rhéaume et al 2015). Déry et al (2015) have created an important new model depicting how urban RNs enact their scope of practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of three generations of nurses, for example, Robson and Robson () found that intention to continue working in the NHS was associated with the combination of attachment to work, importance of work and (low) work–family conflict. Other studies have identified the following factors as associated with intention to remain in practice: perceived support from their organization (Masters & Liu, ), institutional initiatives to support their professional development (Bruyneel, Thoelen, Adriaenssens, & Sermeus, ; Duffield, Baldwin, Roche, & Wise, ; Kenny, Reeve, & Hall, ; Nowrouzi et al., ), a good work environment (Abou Hashish, ; Kenny et al., ; Laschinger, ) and success in or satisfaction with their career (Masters & Liu, ; Osuji, Uzoka, Aladi, & El‐Hussein, ). Factors associated with high staff turnover include exhausting workloads (Havaei, MacPhee, & Dahinten, ), difficulties in managing conflicting demands of work and family (Chen, Brown, Bowers, & Chang, ; Shacklock & Brunetto, ; Yamaguchi, Inoue, Harada, & Oike, ) and insufficient opportunities for professional and career development (Tummers, Groeneveld, & Lankhaar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Equally challenging is the retention of nurses in community settings, with rates of attrition high, especially in areas that are geographically remote or rural (Fadi El‐Jardali et al., ; Keane, Lincoln, Rolfe, & Smith, ; Russell, McGrail, & Humphreys, ). Often nurses working in such contexts cite geographical locations and related factors, such as poor transportation and lack of supportive infrastructure, as reasons for seeking to leave community‐based nursing (AbuAlRub, El‐Jardali, Jamal, Iblasi, & Murray, ; El‐Jardali et al., ; Nowrouzi et al., ). All such work has been useful in pointing to the issues that are commonly encountered in particular settings like lack of support and career development.…”
Section: Introductionmentioning
confidence: 99%